2014
DOI: 10.1094/pdis-07-13-0711-re
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dickeya zeae as a Causal Agent of Bacterial Soft Rot in Banana in China

Abstract: Bacterial soft rot of banana was first noticed in 2009 in Guangzhou city, China. The disease also was observed on various banana cultivars of different genotypes in several other cities. Symptoms of the disease included leaf wilting, collapse of pseudostems, and unusual odor. Five isolated strains that fulfilled Koch's postulates were used for biochemical testing. The five strains were most similar to Dickeya dadantii or D. zeae, but were much less similar to D. paradisiaca when using several phenotype charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 26 publications
3
43
0
1
Order By: Relevance
“…carotovorum clades were found to be more closely related than the necrogenic species, E. mallotivora clade. This result was similar to the findings reported by Ma et al (2007), Pitman et al (2010), and Zhang et al (2014), indicating an ability to discriminate between the soft-rot and necrogenic species.…”
Section: Discussionsupporting
confidence: 91%
“…carotovorum clades were found to be more closely related than the necrogenic species, E. mallotivora clade. This result was similar to the findings reported by Ma et al (2007), Pitman et al (2010), and Zhang et al (2014), indicating an ability to discriminate between the soft-rot and necrogenic species.…”
Section: Discussionsupporting
confidence: 91%
“…The 16S rDNA approach is considered as one of the most widely used standard techniques to infer phylogenetic relationships among bacteria but is sometimes insufficient to distinguish closely related species. The recA and dnaX genes have been proven as powerful markers for inferring bacterial phylogeny and have been used successfully to differentiate species of Dickeya (Samson et al 2005;Slawiak et al 2009;Parkinson et al 2009;Suharjo et al 2014;Zhang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of the host range in this study showed that D. zeae isolated from the pineapple field in Lampung, Indonesia was capable of infecting vegetables, ornamentals, and fruits but unable to infect banana. However, a study by Zhang et al (2014) showed that Dickeya zeae was the causative agent of soft rot disease of banana in China. This difference was an interesting phenomenon showing variation in infection capability within D. zeae species that should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…), is one of the top ten important bacterial phytopathogens in the world, and has been listed as a plant quarantine pest in China since 2007 [ 1 , 2 ]. There are currently 8 species in this genus, including D. dianthicola , D. dadantii , D. zeae , D. chrysanthemi , D. paradisiaca , D. solani , D. aquatic and D. fangzhongdai [ 3 6 ], and among them, D. dadantii , D. zeae and D. solani usually cause devastating disease, resulting in a considerable loss in crop yield, especially on potato, rice and banana [ 7 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Being located in a divergent evolutionary branch, D. zeae bacteria were reported to infect a wide range of plants all over the world, including 4 kinds of natural dicotyledonous hosts such as potato, tobacco, Chrysanthemum and Philodendron , and 6 kinds of natural monocotyledonous hosts such as maize, rice, banana, pineapple, Brachiaria and hyacinth (Additional file 1 ) [ 3 , 8 , 10 , 12 32 ], besides, other 32 kinds of plants were reported as artificial hosts of D. zeae (Additional file 1 ) [ 13 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%